Ethics as a Key Construct in the Resignification of Scientific Praxis in the University Context. (Ágora de Heterodoxias, 2024)
This text, located in the Reflections section of the Scientific Journal Ágora de Heterodoxias, is the product of the author's vision of how ethics represents a transversal component in the research and innovation processes that underpin scientific praxis in the university context. Its elaboration is framed by the invitation received from the Editor-in-Chief of such an important dissemination medium, Dr. Beatriz Carvajal, and its content aims to address some critical-reflective implications around: How to promote creativity and originality in Scientific Research in our Latin American universities, given the increasingly pronounced trend of plagiarism and the promotion of a utilitarian research culture? Also, is the Latin American university responding to the complex socio-productive context with challenging proposals guided by emerging knowledge? The author appreciates the invitation received and reiterates his willingness to continue strengthening academic cooperation relationships with the scientific community of such a prestigious scientific body.
Keywords: Ethics in scientific research; scientific praxis; university research